La guitarrista [book with audioplayer] - Diaz, Lucky ([Library Ideas, LLC], 2024)
"When Canta finds a guitar in the trash, she is one step closer to becoming a rock star. Even though the guitar is broken and she doesn't know how to play, nothing can stop Canta from going after her dreams!"--Provided by publisher.